The Moderating Role of Employee Status on Training Satisfaction and Job Engagement on Turnover Intention - Pramusinto, Benedictus Martyas; Elmi, Farida (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – This study aims to unveiling how training satisfaction and job involvement affect employee turnover intentions at PT MNC Asuransi Indonesia, with employee status as moderator Methodology/approach - The approach used in this study was to collect data from 185 respondents through a questionnaire. Data were analyzed using a descriptive approach to describe the characteristics of the respondents and research variables. In addition, quantitative causal analysis was carried out using the SEM-PLS (Partial Least Square) method to test the research hypothesis. Findings – The results of the analysis show that training satisfaction has a significant negative effect on transfer intentions in general. This finding also applies to both permanent and contract employees. Furthermore, this study also found that job involvement has a significant negative effect on overall turnover intentions. This negative influence also applies to permanent employees and contract employees. Novelty/value – This research makes a new contribution by showing that training satisfaction and job involvement have an important role in reducing employee turnover intention at PT MNC Asuransi Indonesia. However, an interesting finding from this study is that employee status (permanent or contract) does not affect the relationship between training satisfaction and turnover intention, and between work involvement and turnover intention. This means that the influence of the two variables remains the same, regardless of employee status.